Depression among elderly and their perceived social support in a community development block of Purba Bardhaman district, West Bengal: a cross sectional study - Banerjee, Anagh; Goswami, Pramit; Mandal, Sutapa; Taraphdar, Pranita (International Journal Of Community Medicine And Public Health, 2023)
Background: Elderly depression is major public health concern. It causes significant morbidity and mortality burden worldwide. The study aimed to estimate prevalence of elderly depression in a rural area of Purba Bardhaman district, West Bengal and to ascertain their level of perceived social support. Methods: A community-based, cross-sectional study was conducted in Bhatar community development block of Purba Bardhaman district, West Bengal, during period of August 2022 to January 2023. A calculated sample of 238 elderly people were selected by simple random sampling and interviewed with a predesigned, pretested schedule containing geriatric depression scale (GDS-15) for assessing depression, Katz index for independence in activities of daily living (ADL) and multidimensional scale for perceived social support (MSPSS) to assess level of perceived social support. Multivariable logistic regression was done to find out predictors of elderly depression. Results: Out of 238 study participants, 160 (67.2%) were suffering from depression. Prevalence of mild, moderate and severe depression was 49.2%, 14.6% and 3.4% respectively. Low, medium and high level of perceived social support was found in 36.6%, 44.1% and 19.3% study participants, respectively. Impairment in ADL [AOR: 5.045 (2.145-11.868)], presence of financial dependence [AOR: 2.977 (1.330-6.665)], pre-existing one or more co-morbidities [AOR: 2.044 (1.114-3.749)] and educational status below secondary level [AOR: 0.379 (0.199-0.720) were found to be significant predictors of elderly-depression. Conclusions: Prevalence of depression is high among elderly, along with low perceived social support. Health promotion, awareness generation about social security schemes and family support are crucial to prevent elderly depression.